The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1002/ase.1428
|View full text |Cite
|
Sign up to set email alerts
|

Interactive radiological anatomy eLearning solution for first year medical students: Development, integration, and impact on learning

Abstract: A technology enhanced learning and teaching (TELT) solution, radiological anatomy (RA) eLearning, composed of a range of identification-based and guided learning activities related to normal and pathological X-ray images, was devised for the Year 1 nervous and locomotor course at the Faculty of Medicine, University of Southampton. Its effectiveness was evaluated using a questionnaire, pre- and post-tests, focus groups, summative assessment, and tracking data. Since introduced in 2009, a total of 781 students h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 49 publications
5
59
0
2
Order By: Relevance
“…Technological advances offer potential improvement in teaching methods but they need to be evaluated and used appropriately 34,35 . For example, online-learning has been found to be useful in teaching basic knowledge and simple technical skills, but not in understanding complex spatial anatomy 36 .…”
Section: Future Workmentioning
confidence: 99%
“…Technological advances offer potential improvement in teaching methods but they need to be evaluated and used appropriately 34,35 . For example, online-learning has been found to be useful in teaching basic knowledge and simple technical skills, but not in understanding complex spatial anatomy 36 .…”
Section: Future Workmentioning
confidence: 99%
“…Through interactive material in digital repository, immediate feedback and problem solving activities it can catalyse active participation [4,5]. Through computer enabled three-dimensional visualization, it can offset the limitations of verbal descriptions in teaching anatomy [6][7][8][9][10]. For the current tech-savvy generation, it can offer a platform to study through a media they enjoy.…”
Section: The Effectiveness Of Early Clinical Exposure and E-learning mentioning
confidence: 99%
“…Chopra et al found that performance after teaching with computer assisted visual aid was significantly better [8]. Webb and Choi found that the performance of students in summative assessment was better after radiological anatomy e-learning solutions [10]. In the study conducted by Hallgren, the mean scores in both midterm and final exams of the students who had used the web-based instructional materials (Group 1) were significantly higher (28.5 with p<0.001) than the mean scores of those students (Groups 2 & 3) who did not use the material (26 & 24 in midterm and 26 for both groups in final exams) [14].…”
Section: Total Scoresmentioning
confidence: 99%
“…Only 43 % of universities offer e-learning and usually not as a required course. Radiology is particularly suitable for e-learning [24,25] since images can be analyzed and evaluated in a manner very similar to that of actual radiology. E-learning can be helpful not only in student education but also in radiology continuing education [11,26] and in other professions in the healthcare industry [27].…”
Section: Fig 5 Disadvantages Of Integrative Teachingmentioning
confidence: 99%